IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM PEMBELAJARAN ILMU EKONOMI PADA SISWA KELAS X SMA NEGERI 1 DURENAN - Miswanto, Miswanto; Forijati, Forijati; Subagyo, Subagyo (JURNAL ILMIAH EDUNOMIKA, 2024)
To achieve desired results, it is also important to give instructors and students the freedom to develop, discover, and learn on their own. Each school responds to the independent curriculum differently; SMA Negeri 1 Durenan is one of the schools that has succeeded in implementing the curriculum well. The objectives of this research are to: (1) Describe the approach taken in implementing the independent curriculum at SMA Negeri 1 Durenan; (2) Describe the factors that facilitate and hinder the implementation of the independent curriculum at SMA Negeri 1 Durenan; and (3) Describe the impact of implementing an independent curriculum at SMA Negeri 1 Durenan. This research uses descriptive qualitative with interview methods, mile huberman model observation. Data analysis using the data poleulation method. Research findings include: (1) strategies for implementing the independent curriculum at SMA Negeri 1 Durenan; a) internal training workshops; b) workshop on the application of differentiated learning; and c) Project for Strengthening the Profile of Pancasila Students (P5). (2) Inhibiting variables include internal factors originating from student motivation and attitudes and originating from school facilities, while external factors originate from parental support. Supporting elements include the availability of human resources (HR) and supporting digital access. (3) The impact on educators—both principals and instructors, includes creativity, two-way communication that fosters a mindset of readiness to learn, and the search for original ideas. The impact on students, on the other hand, is to concentrate on learning the subject at hand.